Hedging exchange rate risk through foreign debt and use of foreign currency derivatives and its determinants: An Empirical Analysis of UK Non-financial Corporations - Ayala Guerrero, Laura I (2015)
Using detailed, micro-level data on the currency composition of firm’s balance sheets from 245 non-financial firms headquartered in the United Kingdom from 87 different industry sectors between 2005 and 2013, I Investigated the reasons behind a firm’s decision on using foreign debt, or derivative contracts, or a combination of both to hedge their foreign exchange rate risk exposure. Employing panel data analysis with and without time effects this dissertation reached three main findings. First, firms use FX derivatives to hedge their foreign currency exposure and not to speculate, second, in this sample firms with credit rating were found to be more prone to hedge their FX exposure through FX derivatives rather than FX debt, and third, operational and financial hedging strategies are complements rather than substitutes when hedging foreign currency risk.